Preparation method of carbon molecular sieve material, carbon molecular sieve material and application of carbon molecular sieve material
By thermally decomposing phenolic resin in a mixed atmosphere of inert gas and carbon dioxide, a carbon molecular sieve material with suitable pore size was prepared, which solved the problem of uneven pore size distribution of carbon-based adsorbents in the separation of hexafluoropropylene and octafluoropropane, achieved efficient and stable separation effects, and is suitable for industrial applications.
Patent Information
- Application Number
- CN202510644510.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-19
- Publication Date
- 2025-09-30
AI Technical Summary
Existing carbon-based adsorbents have uneven pore size distribution when separating hexafluoropropylene and octafluoropropane, making it difficult to achieve efficient screening and separation. Traditional chemical activation methods also have environmental pollution and high cost problems.
Phenolic resin is used as raw material and pyrolysis treatment is carried out in a mixed atmosphere of inert gas and carbon dioxide to prepare a carbon molecular sieve material with a pore size of 0.50-0.80nm. The size screening effect is used to achieve the separation of hexafluoropropylene and octafluoropropane.
The prepared carbon molecular sieve material has high adsorption selectivity and stability, and can efficiently separate hexafluoropropylene and octafluoropropane at room temperature and pressure. The material structure is stable and suitable for industrial applications.
Smart Images

Figure HDA0005409179160000011 
Figure HDA0005409179160000012 
Figure HDA0005409179160000013
Abstract
Description
Technical Field
[0001] The present application relates to the field of adsorption separation, and specifically to a method for preparing a carbon molecular sieve material, a carbon molecular sieve material and applications thereof. Background Art
[0002] As a critical hardware foundation supporting the artificial intelligence and 5G ecosystems, the semiconductor industry has achieved breakthroughs in atomic-scale manufacturing, with ultra-pure electronic specialty gases (ESGs) becoming a key enabler. This growth trajectory is intrinsically linked to advanced semiconductor manufacturing nodes, where the physicochemical specifications of ESGs, particularly purity, show a strong correlation with process yield metrics. Perfluoropropane (C3F8) is an important plasma etch and chemical vapor deposition (CVD) chamber cleaner, widely used for its excellent etch selectivity, nanoscale aspect ratio control, and low-temperature process compatibility. Industrial synthesis via fluorination of hexafluoropropylene (C3F6) always retains 1-10 mol% of this impurity. The nearly identical physicochemical properties of perfluoropropane and hexafluoropropylene (ΔTbp = 5.7K) fundamentally limit the ability of traditional distillation methods to ultimately remove 90% of the hexafluoropropylene impurity. However, achieving semiconductor-grade purity (5N or 6N and above) requires complex distillation configurations and prohibitively high energy consumption, making the production process economically unsustainable. Relatively speaking, adsorption separation technology has more advantages in removing micro / trace impurities with similar physicochemical properties and structures.
[0003] Ideal adsorption separation is based on the size sieving effect, which can achieve high efficiency and high selectivity compared with thermodynamic / kinetic separation. and Adsorbent materials with sieving separation properties can avoid product loss caused by co-adsorption of the two components. However, this also places stringent demands on the design of the adsorbent's pore structure. Currently, only a few metal-organic frameworks (MOFs), such as Ca-tcpb, Zn-bzc-CF3, CoFA, and Al-PMA, can achieve sieving separation of C3F6 / C3F8 mixtures. This is due to the highly tunable pore structures and pore environment characteristics constructed by MOFs. Although MOFs have demonstrated outstanding separation performance in the separation and purification of C3F6 / C3F8, limitations such as material stability, scalable production, and production costs have limited the industrialization of MOFs. Although molecular sieves generally lack these limitations, the polarized channels and strong adsorption sites induced by metal ions within them are susceptible to strong interactions with olefins such as C3F6, making desorption difficult. Furthermore, high-temperature regeneration is not only energy-intensive but can also lead to thermal polymerization of the olefins. Thanks to the absence of strong adsorption sites on the surface, the regeneration process of porous carbon materials is simple and efficient. Its developed porosity and complex pore structure characteristics make it possible to efficiently separate C3F6 / C3F8.
[0004] Traditional carbon-based adsorbents, due to the complexity of their raw material sources and the uncertainties of the pyrolysis process, produce a wide pore size distribution, making them inadequate for the separation of systems with highly similar molecular sizes and properties, such as C3F6 / C3F8. In contrast, synthetic resins possess highly regular molecular chains and uniform distribution of backbone and functional groups. The resulting carbon materials are structurally uniform and more predictable, demonstrating the great potential of resin-based carbon molecular sieves for the efficient separation of C3F6 / C3F8. Phenolic resin-based carbon molecular sieves, for example, are widely used in nitrogen production by air separation. To overcome the limitations of their small pore size, researchers have proposed two pore size control strategies: physical activation and chemical activation. While chemical activation offers greater control precision, it is limited by the environmental pollution, waste disposal, and equipment corrosion associated with the introduction of chemical activators, which increase the production and use costs of the materials. Therefore, developing adsorbents with high selectivity for hexafluoropropylene and octafluoropropane mixtures using a simpler, less expensive, and safer physical activation method remains a challenge. Summary of the Invention
[0005] To address the above issues, this application proposes a method for preparing a carbon molecular sieve material, a carbon molecular sieve material, and its application. The carbon molecular sieve material provided in this application exhibits high adsorption and separation selectivity for hexafluoropropylene and octafluoropropane. The material's structure and adsorption properties are stable, and it maintains its original adsorption and separation performance even after prolonged exposure to air, suggesting promising prospects for industrial application.
[0006] In a first aspect, the present application provides a method for preparing a carbon molecular sieve material, which comprises subjecting a phenolic resin to a pyrolysis treatment in a first mixed gas, wherein the first mixed gas comprises an inert gas and optionally carbon dioxide.
[0007] The carbon molecular sieve material prepared in this application is prepared by pyrolysis pore-forming treatment of phenolic resin with a three-dimensional network structure as raw material, and a series of carbon molecular sieve materials with pore size distribution are obtained under a pyrolysis atmosphere doped with different proportions of activator (CO2), with a pore size of about 0.50-0.80nm. Hexafluoropropylene with a smaller molecular size can just enter the pores of the carbon molecular sieve material to achieve adsorption, while octafluoropropane with a larger molecular size is difficult to enter the pores and quickly passes through the gaps between the adsorbents. The mechanism of action of molecular sieving makes the adsorption capacity of the two gases on the material have a significant difference. When the mixed gas passes through the adsorption device, octafluoropropane cannot diffuse into the pores of the carbon molecular sieve material and preferentially flows out from the outlet of the device, while hexafluoropropylene is firmly grasped after diffusing into the pores of the carbon molecular sieve material, and the time required to flow out from the outlet of the device is longer, thereby achieving the separation of hexafluoropropylene and octafluoropropane.
[0008] In some embodiments, in the first gas mixture, the volume ratio of the inert gas to the carbon dioxide is (100:0)-(0:100), for example, 100:0, 95:5, 90:10, 85:15, 80:20, 75:25, 70:30, 65:35, 60:40, 55:45, 50:50, 40:60, 30:70, 20:80, 10:90, 0:100, and any value therebetween. In some embodiments, the volume ratio of the inert gas to the carbon dioxide is (5-95):(95-5). In some embodiments, the volume ratio of the inert gas to the carbon dioxide is (75-95):(5-25).
[0009] In some embodiments, the flow rate of the first gas mixture is 10 mL / min-500 mL / min, for example, 10 mL / min, 50 mL / min, 100 mL / min, 150 mL / min, 200 mL / min, 250 mL / min, 300 mL / min, 350 mL / min, 400 mL / min, 450 mL / min, 500 mL / min, and any value therebetween. In some embodiments, the flow rate of the first gas mixture is 25 mL / min-100 mL / min.
[0010] In some embodiments, the inert gas is selected from one or more of nitrogen, argon, and helium.
[0011] In some embodiments, the method for preparing the carbon molecular sieve material comprises the following steps:
[0012] S1: subjecting a phenolic monomer and an aldehyde monomer to a polycondensation reaction to obtain a phenolic resin; preferably, subjecting a first solution containing a phenolic monomer to a polycondensation reaction with a second solution containing an aldehyde monomer in the presence of an alkaline catalyst, a surfactant, and a cross-linking agent to obtain a polycondensation reaction product, and washing and drying the polycondensation reaction product to obtain the phenolic resin;
[0013] S2: subjecting the phenolic resin to a pyrolysis treatment in a first mixed gas, wherein the first mixed gas comprises an inert gas and carbon dioxide.
[0014] In some embodiments, the temperature of the pyrolysis treatment is 700° C.-1200° C., for example, 750° C., 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C., 1100° C., 1150° C., and any value therebetween. In some embodiments, the temperature of the pyrolysis treatment is 800° C.-1000° C.
[0015] In some embodiments, the pyrolysis treatment time is 0.5 h-10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h or 9 h. In some embodiments, the pyrolysis treatment time is 1 h-5 h.
[0016] In some embodiments, the temperature of the pyrolysis treatment is achieved by temperature programming.
[0017] In some embodiments, the heating rate of the programmed temperature is 1°C / min-10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, and any value therebetween. In some embodiments, the heating rate of the programmed temperature is 4°C / min-6°C / min.
[0018] In some embodiments, the phenolic resin is obtained by a condensation reaction of a phenolic monomer and an aldehyde monomer.
[0019] In some embodiments, the phenolic monomer is selected from one or more of monophenolic monomers, bisphenolic monomers, and polyphenolic monomers. In some embodiments, the phenolic monomer is selected from one or more of phenol, resorcinol, and meta-trisphenol.
[0020] In some embodiments, the aldehyde monomer is selected from one or more of C1-C6 aldehyde monomers. In some embodiments, the aldehyde monomer is selected from one or more of formaldehyde, acetaldehyde, and propionaldehyde.
[0021] In some embodiments, the temperature of the polycondensation reaction is 30° C.-120° C., for example, 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., and any value therebetween. In some embodiments, the temperature of the polycondensation reaction is 60° C.-90° C.
[0022] In some embodiments, the polycondensation reaction time is 3 hours to 72 hours, for example, 3 hours, 6 hours, 9 hours, 12 hours, 18 hours, 24 hours, 36 hours, 48 hours, 60 hours, 72 hours and any value therebetween. In some embodiments, the polycondensation reaction time is 12 hours to 36 hours.
[0023] In some embodiments, the polycondensation reaction is refluxed under stirring conditions, preferably at a stirring speed of 50 rpm to 1000 rpm.
[0024] In some embodiments, the molar ratio of the phenolic monomer to the aldehyde monomer is 1:(0.5-5), for example, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:4, 1:5, and any value therebetween. In some embodiments, the molar ratio of the phenolic monomer to the aldehyde monomer is 1:(1-3).
[0025] In some embodiments, the phenolic resin is prepared by the following method:
[0026] A first solution containing phenolic monomers and a second solution containing aldehyde monomers are subjected to a polycondensation reaction in the presence of an alkaline catalyst, a surfactant and a cross-linking agent to obtain a polycondensation reaction product. The polycondensation reaction product is washed and dried to obtain the phenolic resin.
[0027] In some embodiments, the solvent of the first solution is selected from one or more of methanol, ethanol, acetonitrile, acetone, N,N-dimethylformamide, N,N-dimethylacetamide and water, preferably water.
[0028] In some embodiments, the concentration of the phenolic monomer in the first solution is 0.2 mol / L-2.0 mol / L, for example, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, and any value therebetween. In some embodiments, the concentration of the aldehyde monomer in the first solution is 0.5 mol / L-1.0 mol / L.
[0029] In some embodiments, the molar ratio of the phenolic monomer to the solvent in the first solution is 1:(50-2000), for example, 1:50, 1:100, 1:200, 1:300, 1:400, 1:500, 1:1000, 1:1500, 1:2000, and any value therebetween. In some embodiments, the molar ratio of the phenolic monomer to the solvent in the first solution is 1:(100-500).
[0030] In some embodiments, the molar ratio of the phenolic monomer to the alkaline catalyst is (50-500):1, for example, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500:1, and any value therebetween. In some embodiments, the molar ratio of the phenolic monomer to the alkaline catalyst is (100-250):1.
[0031] In some embodiments, the molar ratio of the phenolic monomer to the cross-linking agent is 1:(0.5-5), for example, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:4, 1:5, and any value therebetween. In some embodiments, the molar ratio of the phenolic monomer to the cross-linking agent is 1:(1-2).
[0032] In some embodiments, the molar ratio of the phenolic monomer to the surfactant is (50-500):1, for example, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500:1, and any value therebetween. In some embodiments, the molar ratio of the phenolic monomer to the surfactant is (100-250):1.
[0033] In some embodiments, the solvent of the second solution is selected from water.
[0034] In some embodiments, the weight percentage of the aldehyde monomer in the second solution is 20%-50%, for example, 25%, 30%, 35%, 37%, 40%, 43%, 45%, 47%, or any value therebetween. In some embodiments, the weight percentage of the aldehyde monomer is 5%-45%.
[0035] In some embodiments, the basic catalyst is selected from sodium carbonate and / or potassium carbonate.
[0036] In some embodiments, the surfactant is selected from polyethylene glycol, such as polyethylene glycol 2000.
[0037] In some embodiments, the cross-linking agent is selected from hexamethylenetetramine.
[0038] In some embodiments, washing the polycondensation reaction product comprises first washing with deionized water until the filtrate is colorless and clear to remove residual aldehyde monomers, and then washing with anhydrous ethanol several times to replace residual water.
[0039] In some embodiments, the drying of the polycondensation reaction product is selected from vacuum drying. In some embodiments, the vacuum drying temperature is 30°C-120°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, and any value therebetween. In some embodiments, the vacuum drying temperature is 60°C-90°C.
[0040] In some embodiments, the vacuum drying time is 6 h to 24 h, for example, 6 h, 9 h, 12 h, 15 h, 18 h, 21 h, 24 h, and any value therebetween.
[0041] In some embodiments, the vacuum degree of vacuum drying is 0.08 MPa to 0.1 MPa.
[0042] The carbon molecular sieve material disclosed in this application is prepared using commercially available, inexpensive phenols and aldehydes as raw materials in deionized water, eliminating the need for toxic, volatile, and expensive organic solvents. This results in a material that is both inexpensive and widely available, with relatively mild reaction conditions, convenient operation, simple post-processing, and low synthesis cost. The carbon molecular sieve material disclosed in this application exhibits high adsorption and separation selectivity for hexafluoropropylene and octafluoropropane, and exhibits stable structure and adsorption performance.
[0043] In a second aspect, the present application provides a carbon molecular sieve material prepared according to the preparation method described in the first aspect.
[0044] According to some embodiments of the present application, the pore size (effective micropore size) of the carbon molecular sieve material is For example, 0.50 nm, 0.55 nm, 0.60 nm, 0.65 nm, 0.70 nm, 0.75 nm, 0.80 nm, 0.85 nm, 0.90 nm and any value therebetween. In some embodiments, the pore size of the carbon molecular sieve material is 0.56 nm-0.65 nm.
[0045] According to some embodiments of the present application, the specific surface area of the carbon molecular sieve material is 500m 2 / g-1100m 2 / g, for example, 500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g and any value therebetween. In some embodiments, the specific surface area of the carbon molecular sieve material is 800-1000m 2 / g.
[0046] According to some embodiments of the present application, the shape of the carbon molecular sieve material includes one or more of spherical, columnar, irregular particles or film-like shapes.
[0047] In a third aspect, the present application provides a method for separating hexafluoropropylene and octafluoropropane, which comprises using an adsorbent comprising the carbon molecular sieve material prepared by the preparation method described in the first aspect or the carbon molecular sieve material described in the second aspect to perform adsorption separation on a second mixed gas comprising hexafluoropropylene and octafluoropropane.
[0048] According to some embodiments of the present application, the temperature of the adsorption separation is -5°C to 50°C, for example, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, or any value therebetween. In some embodiments, the temperature of the adsorption separation is 0°C to 40°C. In some embodiments, the temperature of the adsorption separation is 20°C to 30°C.
[0049] According to some embodiments of the present application, the pressure of the adsorption separation is 100 kPa-1000 kPa, for example, 150 kPa, 200 kPa, 250 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa, 700 kPa, 800 kPa, 900 kPa, and any value therebetween. In some embodiments, the pressure of the adsorption separation is 100 kPa-300 kPa.
[0050] According to some embodiments of the present application, the molar percentage of hexafluoropropylene in the second mixed gas is 0.1%-25%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 13%, 15%, 17%, 19%, 20%, 21%, 23%, or any value therebetween. In some embodiments, the molar percentage of hexafluoropropylene is 1%-10%.
[0051] According to some embodiments of the present application, adsorption separation comprises passing a gas mixture containing hexafluoropropylene and octafluoropropane through an adsorption tower or column filled with an adsorbent material. In some embodiments, the adsorption tower may be composed of one or more adsorption towers. In some embodiments, separation is achieved using existing pressure swing adsorption, vacuum pressure swing adsorption, or temperature swing adsorption.
[0052] According to some embodiments of the present application, the adsorptive separation is performed using a fixed bed, wherein the adsorbent is filled in the fixed bed adsorption column.
[0053] According to some embodiments of the present application, the adsorptive separation comprises the following steps:
[0054] The adsorption separation is carried out using a fixed bed, wherein the adsorbent is filled in the fixed bed adsorption column, and preferably comprises the following steps:
[0055] (1) passing a second mixed gas containing hexafluoropropylene and octafluoropropane through a fixed bed adsorption column, wherein small molecular-sized hexafluoropropylene diffuses into the pores of the adsorbent and is adsorbed on the adsorbent, and large molecular-sized octafluoropropane penetrates the adsorption column, thereby obtaining large molecular-sized octafluoropropane;
[0056] (2) desorbing small-molecule hexafluoropropylene from the adsorbent to obtain small-molecule hexafluoropropylene;
[0057] According to some embodiments of the present application, the flow rate of the second mixed gas through the fixed bed adsorption column is 1-50 mL / min / g adsorbent, for example, 5 mL / min / g adsorbent, 10 mL / min / g adsorbent, 20 mL / min / g adsorbent, 30 mL / min / g adsorbent, 40 mL / min / g adsorbent, 50 mL / min / g adsorbent and any value therebetween, preferably 5-25 mL / min / g adsorbent.
[0058] According to some embodiments of the present application, the method further comprises regenerating the adsorbent after the adsorption separation is completed. According to some embodiments of the present application, the regeneration comprises heating the adsorbent to 50°C-250°C under vacuum or inert atmosphere conditions for 2 hours to 72 hours. In some embodiments, the regeneration comprises maintaining the adsorbent at 5°C-30°C under vacuum or inert atmosphere conditions for 2 hours to 72 hours. In some embodiments, the regeneration comprises maintaining the adsorbent at room temperature under vacuum or inert atmosphere conditions for 2 hours to 72 hours.
[0059] Compared with the prior art, this application has the following advantages:
[0060] (1) The raw materials such as phenols and aldehydes used in the preparation of the carbon molecular sieve materials involved in this application are cheap, easily available, and widely available. The synthesis conditions are green and mild, the purification steps are simple, and they are easy to operate and scale up for synthesis.
[0061] (2) The carbon molecular sieve material involved in this application has a stable structure, very high air stability and hydrothermal stability, can screen and separate the mixed gas of hexafluoropropylene and octafluoropropane, and has an extremely high adsorption capacity ratio (hexafluoropropylene / octafluoropropane) at normal temperature and pressure, demonstrating the material's extremely high separation selectivity for the separation of the hexafluoropropylene / octafluoropropane system.
[0062] (3) The carbon molecular sieve material involved in this application has stable performance, good regeneration cycle performance and repeatability, and can maintain its original separation performance after multiple adsorption-regeneration cycles. Its performance in the adsorption separation of hexafluoropropylene and octafluoropropane is far superior to that of most adsorbent materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 The adsorption isotherms of the carbon molecular sieve material RFC-N2 in Example 1 for hexafluoropropylene and octafluoropropane are shown.
[0064] Figure 2 The adsorption isotherms of the carbon molecular sieve material RFC-5CO2 for hexafluoropropylene and octafluoropropane in Example 2 are shown.
[0065] Figure 3 The adsorption isotherms of hexafluoropropylene and octafluoropropane by the carbon material RFC-25CO2 in Example 3 are shown.
[0066] Figure 4 The adsorption isotherms of the carbon molecular sieve material RFC-15CO2 for hexafluoropropylene and octafluoropropane in Example 4 are shown.
[0067] Figure 5 The adsorption cycle isotherm of hexafluoropropylene by the carbon molecular sieve material RFC-15CO2 in Example 4 is shown.
[0068] Figure 6 The adsorption isotherms of hexafluoropropylene and octafluoropropane for different batches of carbon molecular sieve material RFC-15CO2 in Example 4 are shown.
[0069] Figure 7 The adsorption isotherms of the carbon molecular sieve material PFC-15CO2 for hexafluoropropylene and octafluoropropane in Example 5 are shown.
[0070] Figure 8 The adsorption isotherms of the carbon molecular sieve material TFC-15CO2 for hexafluoropropylene and octafluoropropane in Example 6 are shown.
[0071] Figure 9 The low-temperature nitrogen adsorption-desorption curve of the carbon molecular sieve material RFC-N2 in Example 1 is shown.
[0072] Figure 10The low-temperature nitrogen adsorption-desorption curve of the carbon molecular sieve material RFC-5CO2 in Example 2 is shown.
[0073] Figure 11 The low-temperature nitrogen adsorption-desorption curve of the carbon material RFC-25CO2 in Example 3 is shown.
[0074] Figure 12 The low-temperature nitrogen adsorption-desorption curve of the carbon molecular sieve material RFC-15CO2 in Example 4 is shown.
[0075] Figure 13 The low-temperature nitrogen adsorption-desorption curve of the carbon molecular sieve material PFC-15CO2 in Example 5 is shown.
[0076] Figure 14 The low-temperature nitrogen adsorption-desorption curve of the carbon molecular sieve material TFC-15CO2 in Example 6 is shown.
[0077] Figure 15 The fixed bed breakthrough curve of the carbon molecular sieve material RFC-5CO2 for a mixed gas of hexafluoropropylene and octafluoropropane (10 / 90, v / v) in Example 2 is shown.
[0078] Figure 16 The fixed bed breakthrough curve of the carbon material RFC-25CO2 in Example 3 for a mixed gas of hexafluoropropylene and octafluoropropane (10 / 90, v / v) is shown.
[0079] Figure 17 The fixed bed breakthrough curve of the carbon molecular sieve material RFC-15CO2 in Example 4 for a mixed gas of hexafluoropropylene and octafluoropropane (10 / 90, v / v) is shown.
[0080] Figure 18 The fixed bed breakthrough curve of the carbon molecular sieve material RFC-15CO2 for a mixed gas of hexafluoropropylene and octafluoropropane (1 / 99, v / v) in Example 4 is shown.
[0081] Figure 19 The fixed bed breakthrough curve of the carbon molecular sieve material PFC-15CO2 in Example 5 for a mixed gas of hexafluoropropylene and octafluoropropane (10 / 90, v / v) is shown.
[0082] Figure 20 The fixed bed breakthrough curve of the carbon molecular sieve material TFC-15CO2 for a mixed gas of hexafluoropropylene and octafluoropropane (10 / 90, v / v) in Example 6 is shown.
[0083] Figure 21 The fixed bed cycle breakthrough curve of the carbon molecular sieve material RFC-15CO2 for a mixed gas of hexafluoropropylene and octafluoropropane (1 / 99, v / v) in Example 4 is shown. DETAILED DESCRIPTION
[0084] To make the purpose, technical solutions, and advantages of the embodiments of the present application clearer, the technical solutions of the embodiments of the present application will be clearly and completely described below in conjunction with the drawings of the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the described embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0085] In the following examples and comparative examples, unless otherwise specified, pressures are gauge pressures.
[0086] Synthesis method of precursor resorcinol phenolic resin
[0087] Weigh resorcinol (C6H6O2, 10g) into a 500mL three-necked flask, add 200mL of deionized water, and heat and stir in an 80℃ oil bath. After it is fully dissolved, add anhydrous sodium carbonate (Na2CO3, 0.05g), polyethylene glycol 2000 (PEG-2000, 1g) and hexamethylenetetramine (HMTA, C6H 12 N4, 12 g) were added one by one to a three-necked flask. After the solids were fully dissolved, a formaldehyde solution (HCHO, 37-40% by mass, 20 mL) was added dropwise to the three-necked flask and heated under reflux for 24 hours. Finally, the product was poured from the three-necked flask and filtered while hot. After multiple washes with deionized water and anhydrous ethanol, a phenolic resin filter cake was obtained. The resulting material was dried in a vacuum drying oven at 75°C for 12 hours to obtain an orange-yellow phenolic resin powder, designated as resorcinol novolac resin (RF).
[0088] Synthesis method of precursor phenol novolac resin
[0089] Phenol (C6H6O, 8.55 g) was weighed into a 500 mL three-necked flask, and 200 mL of deionized water was added, and the mixture was heated and stirred in an 80°C oil bath. After the mixture was fully dissolved, anhydrous sodium carbonate (Na2CO3, 0.05 g), polyethylene glycol 2000 (PEG-2000, 1 g), and hexamethylenetetramine (HMTA, C6H 12 N4, 12 g) were added one by one to a three-necked flask. After the solids were fully dissolved, a formaldehyde solution (HCHO, 37-40% by mass, 20 mL) was added dropwise to the three-necked flask and heated under reflux for 24 hours. Finally, the product was poured from the three-necked flask and filtered while hot. After multiple washes with deionized water and anhydrous ethanol, a phenolic resin filter cake was obtained. The resulting material was dried in a vacuum drying oven at 75°C for 12 hours to obtain an orange-yellow phenolic resin powder, designated as phenol novolac resin (PF).
[0090] Synthesis method of precursor m-trisphenol phenolic resin
[0091] Weigh m-trisphenol (C6H6O3, 11.45 g) into a 500 mL three-necked flask, add 200 mL of deionized water, and heat in an 80°C oil bath with stirring. After fully dissolved, add anhydrous sodium carbonate (Na2CO3, 0.05 g), polyethylene glycol 2000 (PEG-2000, 1 g), and hexamethylenetetramine (HMTA, C6H 12 N4, 12 g) were added one by one to a three-necked flask. After the solids were fully dissolved, a formaldehyde solution (HCHO, 37-40% by mass, 20 mL) was added dropwise to the three-necked flask and heated under reflux for 24 hours. Finally, the product was poured from the three-necked flask and filtered while hot. The product was then washed with deionized water and anhydrous ethanol multiple times to obtain a phenolic resin filter cake. The resulting material was dried in a vacuum drying oven at 75°C for 12 hours to obtain an orange-yellow phenolic resin powder, designated as m-trisphenol phenolic resin (TF).
[0092] Example 1
[0093] Weigh about 2g of resorcinol phenolic resin powder and place it in a quartz boat, send it into the central heating section of the tubular furnace, set the reaction program, start from room temperature and increase the temperature at a rate of 5℃ / min to 900℃ and maintain it for 3h. The atmosphere used in the pyrolysis and cooling process is high-purity nitrogen, and the gas flow rate is set to 75mL / min. Then take it out for use after natural cooling, and the prepared carbon molecular sieve material is recorded as RFC-N2. The obtained RFC-N2 is vacuum degassed at 200℃ for 4 hours, and then a low-temperature nitrogen adsorption and desorption experiment is carried out. The low-temperature nitrogen adsorption and desorption curve is shown as follows Figure 9 shown.
[0094] The microporosity of RFC-N2 prepared in this embodiment is 100%, and the specific surface area is 771.40m 2 / g, and the main pore size distribution is concentrated in 0.49-0.52nm.
[0095] In order to test the adsorption and separation performance of RFC-N2 prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane were carried out using the RFC-N2 prepared as above as adsorbent. Specifically, 100 mg of adsorbent was taken and the adsorption temperature was set to 25 ° C. Figure 1 The results show that at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reaches 0.05 mmol / g, while the adsorption capacity of octafluoropropane is 0.01 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases is 3.97.
[0096] Example 2
[0097] Weigh about 2g of resorcinol phenolic resin powder and place it in a quartz boat, send it into the central heating section of the tubular furnace, set the reaction program, start from room temperature and increase the temperature at a rate of 5℃ / min to 900℃ and maintain it for 3h. The atmosphere used in the pyrolysis and cooling process is a mixture of high-purity nitrogen and carbon dioxide. The volume ratio of nitrogen and carbon dioxide is 95:5, and the gas flow rate is set to 75mL / min. It is then taken out for use after natural cooling. The prepared carbon molecular sieve material is recorded as RFC-5CO2. The obtained RFC-5CO2 is vacuum degassed at 200℃ for 4 hours, and then a low-temperature nitrogen adsorption and desorption experiment is carried out. The low-temperature nitrogen adsorption and desorption curve is shown as follows. Figure 10 shown.
[0098] The microporosity of RFC-5CO2 prepared in this example is 100%, and the specific surface area is 855.96m 2 / g, and the main pore size distribution is concentrated in 0.52-0.56nm.
[0099] In order to test the adsorption and separation performance of RFC-5CO2 prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane were carried out using the RFC-5CO2 prepared above as an adsorbent. Specifically, 100 mg of adsorbent was taken and the adsorption temperature was set to 25°C. Figure 2 The results show that at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reaches 1.16 mmol / g, while the adsorption capacity of octafluoropropane is 0.03 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases is 40.72.
[0100] In order to test the actual effect of RFC-5CO2 prepared in this example on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above RFC-5CO2 as an adsorbent. In this example, the adsorption separation was performed on a hexafluoropropylene and octafluoropropane mixed gas, the volume ratio of hexafluoropropylene to octafluoropropane was 10:90, the penetration temperature was 25°C, and the pressure was 0.1MPa. The test results are as follows: Figure 15 As shown, when the mixed gas flow rate is 2.0 mL / min, octafluoropropane penetrates immediately, while hexafluoropropylene begins to penetrate at 92.86 min / g. Theoretically, 167.15 L / kg of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 100%.
[0101] Example 3
[0102] Weigh about 2g of resorcinol phenolic resin powder and place it in a quartz boat, send it into the central heating section of the tubular furnace, set the reaction program, start from room temperature and increase the temperature at a rate of 5℃ / min to 900℃ and maintain it for 3h. The atmosphere used in the pyrolysis and cooling process is a mixture of high-purity nitrogen and carbon dioxide. The volume ratio of nitrogen and carbon dioxide is 75:25, and the gas flow rate is set to 75mL / min. It is then taken out for use after natural cooling. The prepared carbon molecular sieve material is recorded as RFC-25CO2. The obtained RFC-25CO2 is vacuum degassed at 200℃ for 4 hours, and then a low-temperature nitrogen adsorption and desorption experiment is carried out. The low-temperature nitrogen adsorption and desorption curve is shown as follows. Figure 11 shown.
[0103] The microporosity of RFC-25CO2 prepared in this embodiment is 100%, and the specific surface area is 1033.85m 2 / g, and the main pore size distribution is concentrated in 0.56-0.62nm and 0.74-0.80nm.
[0104] In order to test the adsorption and separation performance of RFC-25CO2 prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane were carried out using the RFC-25CO2 prepared above as an adsorbent. Specifically, 100 mg of adsorbent was taken and the adsorption temperature was set to 25°C. Figure 3 The results show that at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reaches 2.77 mmol / g, while the adsorption capacity of octafluoropropane is 1.17 mmol / g. The ratio of the adsorption capacity of the adsorbent material to the two gases at 1 bar is 2.36.
[0105] In order to test the actual effect of RFC-25CO2 prepared in this example on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above RFC-25CO2 as an adsorbent. In this example, the adsorption separation was performed on a hexafluoropropylene and octafluoropropane mixed gas, the volume ratio of hexafluoropropylene to octafluoropropane was 10:90, the penetration temperature was 25°C, and the pressure was 0.1MPa. The test results are as follows: Figure 16 As shown, when the mixed gas flow rate is 2.0 mL / min, octafluoropropane penetrates at 14.80 min / g, while hexafluoropropylene begins to penetrate at 214.60 min / g. Theoretically, 359.64 L / kg of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 93.10%.
[0106] Example 4
[0107] Weigh about 2g of resorcinol phenolic resin powder and place it in a quartz boat, send it into the central heating section of the tubular furnace, set the reaction program, start from room temperature and increase the temperature at a rate of 5℃ / min to 900℃ and maintain it for 3h. The atmosphere used in the pyrolysis and cooling process is a mixture of high-purity nitrogen and carbon dioxide. The volume ratio of nitrogen and carbon dioxide is 85:15, and the gas flow rate is set to 75mL / min. It is then taken out for use after natural cooling. The prepared carbon molecular sieve material is recorded as RFC-15CO2. The obtained RFC-15CO2 is vacuum degassed at 200℃ for 4 hours, and then a low-temperature nitrogen adsorption and desorption experiment is carried out. The low-temperature nitrogen adsorption and desorption curve is shown as follows. Figure 12 shown.
[0108] The microporosity of RFC-15CO2 prepared in this embodiment is 100%, and the specific surface area is 958.92m 2 / g, and the main pore size distribution is concentrated in the range of 0.56-0.62nm.
[0109] In order to test the adsorption and separation performance of RFC-15CO2 prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane were carried out using the RFC-15CO2 prepared as above as adsorbent. Specifically, 100 mg of adsorbent was taken and the adsorption temperature was set to 25°C. Figure 4 The results show that at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reaches 2.34 mmol / g, while the adsorption capacity of octafluoropropane is 0.03 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases is 70.48.
[0110] In order to test the repeatability of the adsorption separation performance of different batches of RFC-15CO2 prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane were carried out using RFC-15CO2 produced in different batches as adsorbent. Figure 5 As shown in the results, the adsorption capacity of the adsorbent material for the two gases from different batches is basically consistent.
[0111] In order to test the static adsorption regeneration cycle performance of RFC-15CO2 prepared in this example, the carbon molecular sieve material was subjected to 5 consecutive adsorption-desorption static adsorption cycle tests, as shown in FIG. Figure 6 It is shown that the adsorbent has stable adsorption performance for hexafluoropropylene and has good static cycle performance.
[0112] In order to test the actual effect of RFC-15CO2 prepared in this example on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above RFC-15CO2 as an adsorbent. In this example, the adsorption separation was performed on a hexafluoropropylene and octafluoropropane mixed gas, the volume ratio of hexafluoropropylene to octafluoropropane was 10:90, the penetration temperature was 25°C, and the pressure was 0.1MPa. The test results are as follows: Figure 17 As shown, when the mixed gas flow rate is 2.0 mL / min, octafluoropropane immediately penetrates, while hexafluoropropylene begins to penetrate at 240.00 min / g. Theoretically, 432.00 L / kg of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 100%.
[0113] In order to test the actual effect of RFC-15CO2 prepared in this example on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above RFC-15CO2 as an adsorbent. In this example, the adsorption separation was performed on a hexafluoropropylene and octafluoropropane mixed gas, the volume ratio of hexafluoropropylene to octafluoropropane was 1:99, the penetration temperature was 25°C, and the pressure was 0.1MPa. The test results are as follows: Figure 18 As shown, when the mixed gas flow rate is 6.0 mL / min, octafluoropropane immediately penetrates, while hexafluoropropylene begins to penetrate at 515.78 min / g. Theoretically, 3063.73 L / kg of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 100.0%.
[0114] In order to test the regeneration cycle performance of RFC-15CO2 prepared in this example, the carbon molecular sieve material was subjected to 5 consecutive adsorption-regeneration breakthrough cycle tests. Figure 21 As shown, after undergoing 5 adsorption-regeneration breakthrough cycles, the adsorption performance of the carbon molecular sieve material remains stable and the mixed gas can still be effectively separated.
[0115] Example 5
[0116] Weigh about 2g of phenol-formaldehyde resin powder and place it in a quartz boat, then send it into the central heating section of the tubular furnace, set the reaction program, start from room temperature and heat up at a rate of 5℃ / min to 900℃ and maintain for 3h. The atmosphere used in the pyrolysis and cooling process is a mixture of high-purity nitrogen and carbon dioxide. The volume ratio of nitrogen and carbon dioxide is 85:15, and the gas flow rate is set to 75mL / min. Then take it out after natural cooling and set aside. The prepared carbon molecular sieve material is recorded as PFC-15CO2. The obtained PFC-15CO2 was vacuum degassed at 200℃ for 4 hours, and then a low-temperature nitrogen adsorption and desorption experiment was carried out. The low-temperature nitrogen adsorption and desorption curve is shown in the figure. Figure 13 shown.
[0117] The microporosity of PFC-15CO2 prepared in this embodiment is 100%, and the specific surface area is 656.79m 2 / g, and the main pore size distribution is concentrated in 0.54-0.59nm.
[0118] In order to test the adsorption and separation performance of the PFC-15CO2 prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane were carried out using the PFC-15CO2 prepared above as an adsorbent. Specifically, 100 mg of the adsorbent was taken and the adsorption temperature was set at 25°C. Figure 7 The results show that at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reaches 2.09 mmol / g, while the adsorption capacity of octafluoropropane is 0.03 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases reaches 77.08.
[0119] In order to test the actual effect of the PFC-15CO2 prepared in this example on the separation of a mixture of hexafluoropropylene and octafluoropropane, a fixed bed breakthrough experiment of a mixture of hexafluoropropylene and octafluoropropane was conducted using the above-mentioned PFC-15CO2 as an adsorbent. In this example, the adsorption separation was performed on a mixture of hexafluoropropylene and octafluoropropane, with a volume ratio of hexafluoropropylene to octafluoropropane of 10:90, a breakthrough temperature of 25°C, and a pressure of 0.1 MPa. The test results are as follows: Figure 19 As shown, when the mixed gas flow rate is 2.0 mL / min, octafluoropropane immediately penetrates, while hexafluoropropylene begins to penetrate at 142.38 min / g. Theoretically, 256.28 L / kg of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 100%.
[0120] Example 6
[0121] Weigh about 2g of m-trisphenol phenolic resin powder and place it in a quartz boat, then send it into the central heating section of the tubular furnace, set the reaction program, start from room temperature and increase the temperature at a rate of 5℃ / min to 900℃ and maintain for 3h. The atmosphere used in the pyrolysis and cooling process is a mixture of high-purity nitrogen and carbon dioxide. The volume ratio of nitrogen and carbon dioxide is 85:15, and the gas flow rate is set to 75mL / min. It is then taken out for use after natural cooling. The prepared carbon molecular sieve material is recorded as TFC-15CO2. The obtained TFC-15CO2 is vacuum degassed at 200℃ for 4 hours, and then a low-temperature nitrogen adsorption and desorption experiment is carried out. The low-temperature nitrogen adsorption and desorption curve is shown as follows. Figure 14 shown.
[0122] The microporosity of TFC-15CO2 prepared in this example is 100%, and the specific surface area is 982.33 m2 / g, and the main pore size distribution is concentrated in 0.54-0.64nm and 0.73-0.80nm.
[0123] In order to test the adsorption and separation performance of TFC-15CO2 prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane were carried out using the TFC-15CO2 prepared as above as adsorbent. Specifically, 100 mg of adsorbent was taken and the adsorption temperature was set at 25°C. Figure 8 The results show that at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reaches 2.66 mmol / g, while the adsorption capacity of octafluoropropane is 0.23 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases is 11.57.
[0124] To test the effectiveness of the TFC-15CO2 prepared in this example for separating a mixture of hexafluoropropylene and octafluoropropane, a fixed-bed breakthrough experiment was conducted using the TFC-15CO2 as an adsorbent. In this example, the gas mixture of hexafluoropropylene and octafluoropropane was separated by adsorption. The volume ratio of hexafluoropropylene to octafluoropropane was 10:90, the breakthrough temperature was 25°C, and the pressure was 0.1 MPa. The results are as follows: Figure 20 As shown, when the mixed gas flow rate is 2.0 mL / min, octafluoropropane immediately penetrates, while hexafluoropropylene begins to penetrate at 222.00 min / g. Theoretically, 399.60 L / kg of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 100%.
[0125] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solution of the present application, including combining the various technical features in any other appropriate manner. These simple modifications and combinations should also be regarded as the contents disclosed in the present application and fall within the scope of protection of the present application.
Claims
1. A method for preparing a carbon molecular sieve material, comprising subjecting a phenolic resin to a pyrolysis treatment in a first mixed gas, wherein the first mixed gas comprises an inert gas and optionally carbon dioxide.
2. The preparation method according to claim 1, characterized in that In the first mixed gas, the volume ratio of the inert gas to the carbon dioxide is (5-95):(95-5), preferably (75-95):(5-25); and / or The flow rate of the first mixed gas is 10 mL / min-500 mL / min, preferably 25 mL / min-100 mL / min; and / or The inert gas is selected from one or more of nitrogen, argon and helium.
3. The preparation method according to claim 1 or 2, characterized in that The temperature of the pyrolysis treatment is 700°C-1200°C; preferably 800°C-1000°C; and / or The pyrolysis treatment time is 0.5h-10h, preferably 1h-5h; and / or The temperature of the pyrolysis treatment is achieved by programmed temperature increase. Preferably, the heating rate of the programmed temperature increase is 1°C / min-10°C / min, preferably 4°C / min-6°C / min.
4. The preparation method according to any one of claims 1 to 3, characterized in that The phenolic resin is obtained by polycondensation of phenolic monomers and aldehyde monomers; Preferably, the phenolic monomer is selected from one or more of monophenolic monomers, bisphenolic monomers and polyphenolic monomers, preferably one or more of phenol, resorcinol and meta-trisphenol; Preferably, the aldehyde monomer is selected from one or more C1-C6 aldehyde monomers, preferably one or more formaldehyde, acetaldehyde and propionaldehyde.
5. The preparation method according to claim 4, characterized in that The temperature of the polycondensation reaction is 30°C-120°C, preferably 60°C-90°C; and / or The polycondensation reaction time is 3h-72h, preferably 12h-36h; and / or The molar ratio of the phenolic monomer to the aldehyde monomer is 1:(0.5-5), preferably 1:(1-3); and / or The phenolic resin is prepared by the following method: A first solution containing phenolic monomers and a second solution containing aldehyde monomers are subjected to a polycondensation reaction in the presence of an alkaline catalyst, a surfactant and a cross-linking agent to obtain a polycondensation reaction product. The polycondensation reaction product is washed and dried to obtain the phenolic resin.
6. The preparation method according to claim 5, characterized in that The solvent of the first solution is selected from one or more of methanol, ethanol, acetonitrile, acetone, N,N-dimethylformamide, N,N-dimethylacetamide and water, preferably water; and / or In the first solution, the concentration of the phenolic monomer is 0.2 mol / L-2.0 mol / L, preferably 0.5 mol / L-1.0 mol / L; and / or In the first solution, the molar ratio of the phenolic monomer to the solvent is 1:(50-2000), preferably 1:(100-500); and / or The molar ratio of the phenolic monomer to the alkaline catalyst is (50-500):1, preferably (100-250):1; and / or The molar ratio of the phenolic monomer to the cross-linking agent is 1:(0.5-5), preferably 1:(1-2); and / or The molar ratio of the phenolic monomer to the surfactant is (50-500):1, preferably (100-250):1; and / or The solvent of the second solution is selected from water; and / or In the second solution, the mass percentage of the aldehyde monomer is 20%-50%, preferably 35%-45%; and / or The alkaline catalyst is selected from sodium carbonate and / or potassium carbonate, the surfactant is selected from polyethylene glycol, and the cross-linking agent is selected from hexamethylenetetramine.
7. A carbon molecular sieve material prepared by the preparation method according to any one of claims 1 to 6, Preferably, the specific surface area of the carbon molecular sieve material is 500m 2 / g-1100m 2 / g, preferably 800m 2 / g-1000m 2 / g; Preferably, the pore size of the carbon molecular sieve material is Preferably Preferably, the shape of the carbon molecular sieve material includes one or more of spherical, columnar, irregular particles or film-like shapes.
8. A method for separating hexafluoropropylene and octafluoropropane, comprising using an adsorbent comprising the carbon molecular sieve material prepared by the preparation method according to any one of claims 1 to 6 or the carbon molecular sieve material according to claim 7 to perform adsorption separation on a second mixed gas containing hexafluoropropylene and octafluoropropane.
9. The method according to claim 8, characterized in that The temperature of the adsorption separation is -5°C to 50°C, preferably 0°C to 40°C, more preferably 20°C to 30°C; and / or The pressure of the adsorption separation is 100 kPa-1000 kPa, preferably 100 kPa-300 kPa; and / or In the second mixed gas, the molar proportion of hexafluoropropylene is 0.1%-25%, preferably 1%-10%; and / or The adsorption separation is carried out using a fixed bed, wherein the adsorbent is filled in the fixed bed adsorption column, and preferably comprises the following steps: (1) passing a second mixed gas containing hexafluoropropylene and octafluoropropane through a fixed bed adsorption column, wherein small molecular-sized hexafluoropropylene diffuses into the pores of the adsorbent and is adsorbed on the adsorbent, and large molecular-sized octafluoropropane penetrates the adsorption column, thereby obtaining large molecular-sized octafluoropropane; (2) desorbing small-molecule hexafluoropropylene from the adsorbent to obtain small-molecule hexafluoropropylene; Preferably, the flow rate of the second mixed gas through the fixed bed adsorption column is 1-50 mL / min / g adsorbent.
10. The method according to claim 8 or 9, characterized in that The method further includes regenerating the adsorbent after the adsorption separation is completed. Preferably, the regeneration includes heating the adsorbent to 50°C-250°C under vacuum or inert atmosphere conditions and maintaining it for 2h-72h; or the regeneration includes maintaining the adsorbent at 5°C-30°C under vacuum or inert atmosphere conditions for 2h-72h.